Unemployment During the Recent COVID-19 Pandemic: Exploring the Perspective of Fresh Graduates from a Developing Nation - Momen Md. Abdul; Shahriar Shamsul Huq Bin; Naher Nazmun; Nowrin Nafisa (Economics and Business)
The recent COVID-19 pandemic has accelerated the radical changes in economics, labour market and business models globally. The job market is no exception. This study aims to find out what factors affect job opportunities for recent graduates during a pandemic. It is a quantitative study in which 200 recent graduates were randomly chosen. Factor analysis, both exploratory and confirmatory, was used. The study tests the hypothesis and confirms the contributing factors to the unemployment problem by conducting a path analysis using structural equation modelling (SEM). It is hard for recent graduates to get jobs because of economic and personal reasons during this pandemic. On the other hand, the study does not think that social issues play a significant role. The study will aid similar groups in comprehending the phenomena and devising strategies to overcome their causes. A future study could compare the underlying issues in various countries. This paper, among the very few studies, will assist the stakeholders in comprehending the job market in a developing country during the ongoing COVID-19 pandemic, particularly from the perspective of a recent graduate.